Experiences in developing and applying decision support systems for strategic flood risk management. Issue 3 (3rd July 2018) - van der Most, H.; Asselman, N.; Slager, K.
ABSTRACT: Decision support systems (DSSs) have been developed for many years. Their main goal was originally to support decision-makers. Reviews show, however, that the actual use of most DSSs did fall short of these ambitions. The goal of DSSs has gradually shifted to enhancing stakeholder engagement for better informed and societally supported decisions. In this paper, we present and discuss a DSS which has been extensively used by a large and diverse group of stakeholders. This so-called Planning Kit Room for the River did successfully support the development of alternative strategies for flood risk management of the riverine area in the Netherlands. Based on these strategies a major investment programme was developed, which has been implemented recently, within time and budget. In the paper, we explore the key factors for its successful application. Based on this analysis and our experience with both interactive planning processes and DSSs, we propose a typology of DSSs for strategic planning of flood risk management. We outline three types of DSSs with different set-ups and associated users, including a DSS based on an integrated model system. The paper concludes with a discussion of the main characteristics and the potential and limitations of these types of DSSs from both a user and a hydro-informatics perspective.